System specifications for developing an Automatic Dependent Surveillance-Broadcast (ADS-B) monitoring system - Ali, B.S. (Elsevier, 2016)
Automatic Dependent Surveillance-Broadcast (ADS-B) is a surveillance system placed in aircraft that periodically transmits state vector estimates and other information to air traffic control centers and other nearby aircraft (and may also receive traffic and weather information from various entities). The state vector estimates are derived from navigation avionics and are transmitted via a common communications channel, which means that ADS-B is highly dependent on aircraft navigation and communication systems. ADS-B also requires ground stations to receive information from aircraft. As a result of this complex architecture, the ADS-B system is prone to various failure modes.